The lichens of Ukrainian-Swiss model area in the Ugolsky Massive of Karpatsky Biosphere Reserve (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The Ukrainian-Swiss model area of the Ugolsky massive of Karpatsky Biosphere Reserve are represent 65 species of the lichens from 43 genera and 25 families. 47 corticolous species are typical lichens of the lower tier in the dark primeval Fagus forest on the mountains slopes of the reserve. 18 saxicolous species were found on limestone outcrops of the model area. Bacidia subincompta (Nyl.) Arnold, Belonia herculina (Rehm ex Lojka) Hazsl, Biatora chrysantha (Zahlbr.) Printzen, Melaspilea gibberulosa (Ach.) Zwackh and Pyrenula nitida are lichen indicators of the ecological continuity of the mature primeval forest of the East Carpathians.
Keywords: lichens, indicator species, primeval forests, Ugolsky massive, Carpathian Biosphere reserve.